Gaia and variable stars. Issue Volume 9:Issue S298(2013) (6th January 2014) - Eyer, Laurent; Holl, Berry; Mowlavi, Nami
Abstract: The study of variable phenomena (periodic, irregular or transient) provides a unique way to acquire knowledge about objects in our Universe. Currently, we are going through a rapid expansion of time-domain astrophysics. One reason for this expansion is the technological developments materialised in small to medium size observational projects such as HAT, OGLE, Catalina, PTF and upcoming very large projects such as Gaia or LSST. In this article, we are focusing on the ESA cornerstone mission Gaia. This spacecraft will provide astrometric, photometric and spectroscopic measurements for one billion stars. Among the existing and planned multi-epoch projects Gaia is unique because it will provide exquisite astrometric measurements for all objects it observes. We provide a brief overview of the literature concerning this mission and its expected contribution to variability studies.